Epistaxis after nasal surgery: incidence and risk factors - Pinto, Isabel (2019)
Objectives: To determine the incidence of epistaxis after nasal surgery as well as possible risk factors for its occurrence. Material and methods: Retrospective study of all patients submitted to nasal surgery at the Otorhinolaryngology Department of Vila Nova de Gaia/Espinho Hospital Center during a period of 16 months. Results: A total of 412 patients were included. The incidence of epistaxis was 4.6%. The type of surgery most frequently associated with bleeding was septoplasty (57.9%) followed by septoplasty with endoscopic sinus surgery (31.6%). The analysis of the possible risk factors concluded that the type of nasal packing presented a statistically significant association with the occurrence of epistaxis (p=0.011). Conclusions: Epistaxis after nasal surgery is an uncommon event. Some of the classic risk factors associated with epistaxis on patients without previous history of nasal surgery may not apply to postoperative epistaxis.